DESIGNING AN E-BANK OF READING EXERCIES OF NARRATIVE TEXTS FOR THE STUDENTS OF GRADE X - Yulia Sri Wulandari; Achmad Fanani; Trikaloka Handayani Putri (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
This current research was conducted to design a teaching medium for teaching reading on narrative texts for grade X. The methodology applied in the research is a 'design research methodology' covering three phases: Preliminary Research; Design Phase; and Assessment Phase. Based on interview with the teacher, the needs could be identified as follow: there was no appropriate media used in teaching reading, the books used not sufficient for students to practice, e-bank can be applied in the class, reading text was needed narrative text, media can used offline, and provide 100 more exercise practice for e-bank. After getting information about the needs, the product was designed and developed based on them. After the prototype was created it was then validated by an expert. In general, the expert?s evaluation was concerned with: the grammatical error and adding more questions about main idea and generic structure. Besides it was also suggested to add sound in the text. The final stage was done through an assessment by the teacher (the end user of the product). The benefit of this research is to make it the teacher have alternative teaching materials and easy to access because they are too easily accessible via mobile phones. And also the students can use in practicing various questions about reading narrative text more easily.